(untitled) (American Journal of Interdisciplinary Research and Innovation, 2025)
The study was undertaken to describe the teachers’ level of competence in oral language teaching. Specifically, it assessed the teachers’ level of competence in oral language teaching strategies in terms of the promotion of auditory memory, development of listening and speaking skills, teaching and extending of vocabulary and conceptual knowledge, creation of a language learning environment, and teaching of a variety of spoken text. Using total enumeration, 44 Grade 5 English from the public elementary schools of the Schools Division of Laoag City served as the respondents in this study. A survey questionnaire was utilized to gather the needed data on the teachers’ level of competence in the oral language teaching strategies, along with the five components of effective oral language instruction. Overall, the teachers are moderately competent in using the oral language teaching strategies, as reflected in the overall mean of 3.49. The teachers are moderately competent in three of these components – development of listening and speaking skills (x=3.48); teaching and extending of vocabulary and conceptual knowledge (x=3.48); and teaching of a variety of spoken texts (x=3.43).